Synthesis, characterization and thermal properties of thiosalicylate ionic liquids - Wilfred, C.D. (Springer India, 2013)
In an attempt to produce new functionalized ionic liquids, a series of thiosalicylate ionic liquids based on imidazolium, ammonium, phosphonium, choline and pyrrolidinium cations were synthesized. The compounds were characterized by Infra Red (IR), Nuclear Magnetic Resonance (NMR) and mass spectra (ESI-MS). Their glass-transition temperatures, melting points and decomposition temperatures have been measured. Physicochemical properties of ionic liquids are influenced by alkyl chain length and nature of the cation of ionic liquids. Â© Indian Academy of Sciences.